Rietveld analysis of CaCu3Ti4O12 thin films obtained by RF-sputtering - Foschini, C. R. [UNESP]; Tararam, R. [UNESP]; Simões, A. Z. [UNESP]; Rocha, L. S. [UNESP]; Santos, C. O.P. [UNESP]; Longo, E. [UNESP]; Varela, J. A. [UNESP] (Springer Nature, 2016)
Calcium copper titanate, CaCu3Ti4O12, CCTO, thin films with polycrystalline nature have been deposited by RF sputtering on Pt/Ti/SiO2/Si (100) substrates at a room temperature followed by annealing at 600 °C for 2 h in a conventional furnace. The crystalline structure and the surface morphology of the films were markedly affected by the growth conditions. Rietveld analysis reveal a CCTO film with 100 % pure perovskite belonging to a space group Im3 and pseudo-cubic structure. The XPS spectroscopy reveal that the in a reducing N2 atmosphere a lower Cu/Ca and Ti/Ca ratio were detected, while the O2 treatment led to an excess of Cu, due to Cu segregation of the surface forming copper oxide crystals. The film present frequency -independent dielectric properties in the temperature range evaluated, which is similar to those properties obtained in single-crystal or epitaxial thin films. The room temperature dielectric constant of the 600-nm-thick CCTO films annealed at 600 °C at 1 kHz was found to be 70. The leakage current of the MFS capacitor structure was governed by the Schottky barrier conduction mechanism and the leakage current density was lower than 10−7 A/cm2 at a 1.0 V. The current–voltage measurements on MFS capacitors established good switching characteristics.